Antitumor Activity of Natural Products and Related Compounds - De Filippis, Barbara; Ammazzalorso, Alessandra; Fantacuzzi, Marialuigia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Cancer is one of the leading causes of morbidity and mortality in humans today, and the number of people affected by cancer is growing. As a result, the search for new antitumor agents that may be more effective and secure than existing treatments is an ongoing effort. Nature provides a wide range of compounds with a great variety of chemical scaffolds and distinct bioactivity profiles. Indeed, natural products are a rich source of bioactive molecules that, over the years, have found application in the treatment of many diseases, including cancer. Natural products have played an important role in chemotherapy and chemoprevention by providing antitumor drugs such as camptothecin, doxorubicin, paclitaxel, vinblastine, and vincristine, as well as understanding the cellular and molecular mechanisms underlying antitumor activity. Significant advances in natural source isolation and extraction techniques have enabled the identification of novel lead compounds as useful starting points for the generation of optimized molecules with enhanced therapeutic potential via semi-synthetic or synthetic processes. The focus of this Topic is on natural substances derived from plants or animals, as well as their synthetic derivatives, which have been investigated for their ability to counteract cancer progression.